Oral Pigmented lesions- A Short Review - Ryhanath Gulshan1 , K.M.K.Masthan2 , .N.Aravindha Babu3 , L.Malathi3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Pigmentations can be commonly found in the mouth which are presents in various clinical patterns rangingfrom physiological changes to oral manifestations of systemic diseases and malignancies. Oral pigmentationcan be focal,multifocal or diffuse. Oral pigmentation can be exogenous, endogenous, physiological andpathological. Oral pigmentation is more likely to have a multifactorial etiology